Построение блочно-ациклической схемы несогласованной базы данных - Шахова, О. И. (ХНУРЕ, 2012)
The article deals with one class of the circuits of databases, namely - class of the not cyclic circuits having several desirable properties will be considered. These properties are formulated as conditions, which should be carried out for all databases with such circuit.
Keywords: редукции Грэхема; схема отношения; атрибут; циклическая схема